Histopathological evaluation of the intestine of jabutis (Chelonoidis carbonarius e Chelonoidis denticulatus) reared in captivity and parasitized by helminths (Chapiniella variabilis and Atractis thapari) - Simone, Simone Mousinho (2019)
The aim of this study was to identify and describe intestinal lesions caused by helminths in red-footed tortoise (Chelonoidis carbonarius) and yellow-footed tortoise (Chelonoidis denticulatus) reared in captivity in the Zoo and Botanical Park of Teresina, Piauí State, Brazil. The parasitological evaluation of 142 of these tortoises revealed that all were parasitized by helminths (ascarids and strongyles), which were identified as Atractis thapari and Chapiniella variabilis by light and electron microscopy. The 12 most parasitized tortoises (six per species) were euthanized, and samples of small and large intestine were evaluated by histopathology. Macroscopically, all small and large intestines had hyperaemia. Microscopically, hyperaemia (12/12), diffuse goblet cell hyperplasia (8/12) and submucosa oedema (1/12) were observed in the small intestine. Hyperaemia was observed in the large intestine, varying from discrete to intense (12/12) and focally extensive and severe transmural granulomatous enteritis (1/12).